Hubungan Personal Hygiene dan Penggunaan APD dengan Keluhan Penyakit Kulit pada Pemulung di TPA Sampah - Nadia Rahmagina; Awalia Gusti; Sari Arlinda (Jurnal Sehat Mandiri, 2024)
Skin diseases are one of the occupational diseases that can be caused by poor personal hygiene and inadequate use of personal protective equipment (PPE). For scavengers, maintaining personal hygiene and using PPE is crucial since they interact directly with waste. This study aims to determine the relationship between personal hygiene behavior, PPE use, and complaints of skin diseases among scavengers at the Air Dingin landfill in Padang City in 2024. The research method used is quantitative analytic with a cross-sectional approach. The population consists of 98 respondents, with a sample of 87 respondents. The instruments used were questionnaires and observation sheets, and data analysis was performed using the chi-square test. The results showed a significant relationship between personal hygiene and PPE use with skin disease complaints among scavengers (p-value = 0.0001). The OR values for personal hygiene = 12.264 and for PPE use = 10.038. It can be concluded that personal hygiene and PPE use are related to skin disease complaints among scavengers. It is hoped that scavengers at the Air Dingin landfill will pay more attention to personal hygiene and consistently use complete PPE.